CHARACTERIZATION OF LONGITUDINAL PROFILES OF RIVERS APPLIED TO THE STUDY OF MORPHOSTRUCTURAL AND MORPHOTECTONIC INFLUENCE IN THE RELIEF OF THE CENTRAL SECTOR OF THE ARAUCARIA PLATEAU - SOUTHERN BRAZIL - Lima, Jacson Gosman Gomes de; Pontelli, Marga Eliz; Santos Matos, Andrea Cristina Lima dos (Ra'e Ga: o Espaço Geográfico em Análise, 2023)
Longitudinal profiles were analyzed in the rivers of the central sector of the Araucaria Plateau, aiming to contribute to the understanding of the morphostructural and morphotectonic influence on the relief. Radar images were used to extract the drainage network and contour lines. Channels above the 4th order were considered, in which geological formations and structures were plotted. The results showed that rivers on a single lithology are more at equilibrium, or graded, with less pronounced slope breaks (knickpoints). Those with greater lithological differentiation, on the other hand, have less channel balance and more marked knickpoints. Structural factors are also important, as the main breaks in rivers are associated with lineaments (70%). The sections in ascension and subsidence along the rivers have a strong correlation with geological structures (52%), being more expressive in the Chapecó River basin (72%). This suggests that the study area was subject to morphostructural and morphotectonic influence, with the Chapecó basin being the most affected.